Comparison of quantitative stenosis characteristics at routine coronary computed tomography angiography with invasive fractional flow reserve for assessing lesion-specific ischemia - Wang, Rui; Baumann, Stefan (Journal of cardiovascular computed tomography, 2015)
Objective: To comprehensively evaluate quantitative parameters derived from routine coronary CT angiography (cCTA) for predicting lesion-specific ischemia in comparison to invasive fractional flow reserve (FFR). Background: The ability of cCTA to gauge lesion-specific ischemia is limited. Several quantitative parameters have been proposed to enhance the specificity of cCTA, such as morphologic indices (lesion length/minimal lumen diameter4 [LL/MLD4]; percentage aggregate plaque volume [%APV]) and a measure of intracoronary contrast gradients (corrected coronary opacification [CCO]). Methods: Forty-nine patients who had undergone cCTA followed by FFR within 3 months were included. An experienced observer visually assessed all cCTA studies and derived multiple measures characterizing the lesion of interest, including LL, MLD, minimal lumen area (MLA), LL/MLD4, remodeling index, %APV, and CCO. Lesion-specific ischemia was considered with FFR <0.8. Results: Among 56 lesions, 13 were flow-obstructing by FFR. On univariate analysis, LL, MLD, LL/MLD4, and CCO showed discriminatory power. The area under the curve of LL/MLD4 (0.909) was significantly greater compared with MLD (0.802, P = 0.014), LL (0.739, P = 0.041), and CCO (0.809), although the latter did not reach statistical significance (P = 0.175). On multivariate regression, LL/MLD4 was the only independent predictor of lesion-specific ischemia (odds ratio 2.021, P = 0.001). Moreover, LL/MLD4 compared favorably to visual cCTA evaluation. Conclusion: LL/MLD4 derived from routine cCTA can enhance the detection of lesion-specific ischemia and may be superior to other described quantitative parameters.
Gesehen am 25.01.2018